2017
DOI: 10.1371/journal.pone.0174002
|View full text |Cite
|
Sign up to set email alerts
|

Retention and sustainability of community-based health volunteers' activities: A qualitative study in rural Northern Ghana

Abstract: BackgroundThe shortage of formal health workers has led to the utilization of Community-Based Health Volunteers (CBHV) to provide health care services to people especially in rural and neglected communities. Community-based health volunteers have been effective partners in health care delivery at the community level for many years. The challenge is how to retain these volunteers and also sustain their activities. This study explored factors affecting retention and sustainability of community-based health volun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 12 publications
1
38
0
7
Order By: Relevance
“…The CCMm system should involve the clinicians so that the CHWs are well incorporated into the system for effective management of malaria in communities. The respect and support from qualified health workers and the health system is essential to the success and retention of health volunteers (4,(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…The CCMm system should involve the clinicians so that the CHWs are well incorporated into the system for effective management of malaria in communities. The respect and support from qualified health workers and the health system is essential to the success and retention of health volunteers (4,(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, their family members did not support them in continuing as VHWs, similar to studies conducted in Bangladesh 47 and Kenya. 48 However, a study conducted in Tanzania found that they received support from family members including spouse which is truly encouraging and inspiring. 49 The findings from this study established that the non-provision of a regular salary and travel allowances were sources of discouragement and frustration.…”
Section: Discussionmentioning
confidence: 99%
“…Sebagian besar relawan yang dropout mengatakan kurangnya dukungan dan rasa hormat dari anggota masyarakat membuat mereka berhenti bekerja sebagai sukarelawan kesehatan. 6 Peran untuk pekerja kesehatan masyarakat termasuk mempromosikan perawatan primer, mendorong pengujian, memberikan pendidikan dan memfasilitasi keterlibatan dalam perawatan. Sementara berbagai aspek fasilitasi pekerja kesehatan masyarakat ditemukan, beberapa hambatan/ masalah dengan pelatihan dan kerahasiaan.…”
Section: Hasil Analisis Univariat Dan Bivariatunclassified